СПОСІБ РЕАГУВАННЯ НА КОНФЛІКТНУ СИТУАЦІЮ У ЮНАКІВ - Яцюк , Анастасія Миколаївна (Insight: the psychological dimensions of society, 2019)
Тhe results of the empirical research of conflict behavior, coping strategies and personality traits The article presents.The purpose of the article was to establish the interdependence of these indicators. The study was conducted at the Kherson State University. The sample consisted of students aged 19 to 23 years.Methods. In this research work the following methods and techniques have been used: the copy-test of R. Lazarus, adapted by T. Kryukov, E. Kuftyak and M. Zamyshlyaeva; the method of K. Thomas, in the adaptation of N. Grishina "The style of conflict behavior"; R. Kettel's 16th Factor Questionnaire; "Personal Questionnaire" by G. Aizenk. As a mathematical method, a linear r-Pearson correlation coefficient has been selected. The main part of the article presented the results of correlation analysis. The rivalry style is matched by the confrontation coping strategy; style of cooperation eliminates the possibility of using self-control copies, accepting responsibility and distance; compromise eliminates confrontation and positive reappraisal; the style of the assignment positively correlates with coping strategies of self-control, acceptance of responsibility, distance and negatively correlates with confrontation; the evasion style had no statistically significant correlation. A correlation between the behavior styles and the “H” and “E” factors among the personality traits has been established. Rivalry is responsible for courage and dominance, while the style of conduct is characterized by timidity.Results. The research has found that the rivalry style corresponds to the type of temperament choleric, and the phlegmatic type of temperament has a negative correlation. The scientific novelty of the work is that, for the first time, the correlation between conflict behavior styles and coping strategies has been explored at the empirical level, which makes it possible to explore the problem more broadly.Conclusions. The results obtained can be used for further psychological research, development of diagnostic and therapeutic tools.
Keywords: стиль поведінки в конфлікті, копінг-стратегія, конфронтація, суперництво, компроміс, поступки, співпраця